The Sharing Economy in Europe: Developments, Practices, and Contradictions - Vida Česnuitytė; Andrzej Klimczuk; Cristina Miguel; Gabriela Avram (Palgrave Macmillan, 2022)
This open access book considers the development of the sharing and collaborative economy with a European focus, mapping across economic sectors, and country-specific case studies. It looks at the roles the sharing economy plays in sharing and redistribution of goods and services across the population in order to maximise their functionality, monetary exchange, and other aspects important to societies. It also looks at the place of the sharing economy among various policies and how the contexts of public policies, legislation, digital platforms, and other infrastructure interrelate with the development and function of the sharing economy. The book will help in understanding the future (sharing) economy models as well as to contribute in solving questions of better access to resources and sustainable innovation in the context of degrowth and growing inequalities within and between societies. It will also provide a useful source for solutions to the big challenges of our times such as climate change, the loss of biodiversity, and recently the coronavirus disease pandemic (COVID-19). This book will be of interest to academics and students in economics and business, organisational studies, sociology, media and communication and computer science.
Keywords: D16; L86; Z18; Z13; 330; collaborative economy; sharing economy; collaborative consumption; peer-to-peer economy; digital platforms; social innovation; socio-technical systems; open access